Hydrothermal synthesis of needle-like nanocrystalline zeolites from metakaolin and their applications for efficient removal of organic pollutants and heavy metals - Luo, Hongwei (2019)
In this study, an environment-friendly and sustainable route to convert clay minerals into highly efficient sorbents for organic pollutants and heavy metals removal was reported. Needle-like nanocrystalline zeolites were hydrothermally synthesized from metakaolin (MK) and their properties and efficiency for organic pollutants and heavy metals removal were investigated. After hydrothermal treatment, the morphology of metakaolin markedly transformed from layered structures to aggregations of needle-like zeolites, thereby resulting in substantial increases of total and meso porosities, N2 sorption capacity and specific surface area. The hydrothermally synthesized MK-based zeolites exhibited much stronger sorption capacity toward aniline (AN), 3-chloroaniline (3-CA), and humic acid (HA). The electrostatic attraction and surface complexation dominated by chemisorption likely accounted for the enhanced sorptive interactions between zeolites and organic compounds. Similarly, the adsorption capacity of the newly formed zeolites toward Cu(II) and Pb(II) increased almost 20-fold, which was 431.0 mg g−1 for Cu(II) and 337.8 mg g−1 for Pb(II). Ionic exchange reactions between heavy metal ions and the enriched sodium ion resulted in heavy metal removal by the MK-based zeolites. Thus, the hydrothermally synthesized MK-based zeolites may be employed as sorbents for wastewater treatment to remove organic pollutants and heavy metals with no significant toxicity risk.